Prevalence, knowledge and perception of self medication practice among undergraduate healthcare students (2021)
Background: Globally, self-medication is a common practice, and an increasingly perceived necessity to relieve bur dens on health services. However, inappropriate self-medication may result to reduced health outcomes, increased antimicrobial resistance and economic waste. Healthcare students are the future health professionals who will be consistently responsible for educating the public on rational use of medication. This study therefore aimed to assess the prevalence, knowledge and perception of self-medication practices among healthcare students. Methods: A cross-sectional study was carried out among 866 healthcare students in a Nigerian University, compris ing medical, nursing and pharmacy students. Information was garnered from respondents using a self-administered questionnaire. Data were summarized with descriptive statistics, while Chi-square and logistic regression tests were used for categorical variables at p< 0.05. Results: Mean age was 21±2.8 years, and female respondents were 447 (51.6%). Prevalence of self-medication among respondents was 473 (54.6%). A total of 288 (55.3%) demonstrated good knowledge of self-medication prac tices, comprising 250 (52.2%) among those who have previously self-medicated and 229 (47.8%) among those who had not. Reasons for engaging in self-medication practices were mentioned to include treatment of minor ailments (357; 32.4%), while 248 (22.5%) believed they had the medical knowledge of what to use. Analgesic (353; 30.1%), anti malarial (352; 30.0%), and antibiotics (182; 15.5%) were the commonest classes of medication used for self-medication. Headache (363; 18.4%), malaria (334; 16.9%), and cough (184; 9.3%) were the most frequently treated conditions. More than half (281; 59.4%) of the respondents’ purchased their self-medicated drugs from the community pharmacy. Gen der and respondents’ disciplines were found to be the independent predictors for good knowledge of self-medication practice. Conclusion: Prevalence of self-medication among the studied healthcare students is moderately high, while approximately half demonstrates good knowledge and perception of self-medication practices. Stimulation for selfmedication practice largely arise from the perception of treating minor ailments. This underscores a need for advo cacy on responsible self-medication practice during the formal training of these future health professionals, in order to avert its imminent/widespread negative consequences.